2013
DOI: 10.4244/eijv9i4a74
|View full text |Cite
|
Sign up to set email alerts
|

Two-year outcomes of everolimus vs. paclitaxel-eluting stent for the treatment of unprotected left main lesions: a propensity score matching comparison of patients included in the French Left Main Taxus (FLM Taxus) and the LEft MAin Xience (LEMAX) registries

Abstract: ULM stenting with EES is safer and more effective than PES with a reduction in TLF by 53% at two years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 29 publications
1
12
0
3
Order By: Relevance
“…Our low events rate were in agreement with several randomized and observational studies comparing 2nd or 3rd generation DES versus the first ones , although limited information has been reported so far in patients with complex lesion subsets such as we are reporting here . The 2nd and 3rd generation DES showed significant improvement in stent design, polymer characteristics, drug release and stent struts coverage, and all of these new features significantly enhanced the safety/efficacy compared to previous ones .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our low events rate were in agreement with several randomized and observational studies comparing 2nd or 3rd generation DES versus the first ones , although limited information has been reported so far in patients with complex lesion subsets such as we are reporting here . The 2nd and 3rd generation DES showed significant improvement in stent design, polymer characteristics, drug release and stent struts coverage, and all of these new features significantly enhanced the safety/efficacy compared to previous ones .…”
Section: Discussionsupporting
confidence: 91%
“…In that study, there was an incidence of the primary end point of MACCE at 1 year of follow‐up among patients treated with 1st generation DES (12% of MACCE and 7% of death/MI/CVA). Taking into account that second generation DES—either Xcience V (Abbott,Vascular), Promus Element (Boston Scientific), or Endeavor Resolute (Medtronic)—compared to the 1st generation ones, Taxus Express or Taxus Element (Boston Scientific) in most cases, reported a reduction of major adverse events of 50% during the first and second year , using a two‐sided test for differences in independent binomial proportions with a level of 0.05, we estimated that if we included 225 patients, the power of the study would be 80% to detect differences between both kind of stents. Continuous variables were compared using ANOVA with Bonferroni correction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moynagh et al [10] reported a propensity score matching comparison between PES and EES for the treatment of unprotected left main disease, however we compared firstgeneration DES and second-generation DES for treating not only LM but also 3VD using propensity matching according to SYNTAX scores. The main findings of our study are:…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that improved clinical outcomes with the everolimus-eluting stent --the most used stent in Nfor et al's study (~59% 32 ) --in multivessel disease, 37 coupled with similarly reported data from the French Left Main Taxus and LEMAX registries that investigated left main stenting with everolimus-eluting stents 38,39 and the known reductions in stent thrombosis of newer-generation DES, [40][41][42][43][44][45][46][47] implies that if newergeneration DES had been used in the SYNTAX trial, there would have been a significant reduction in repeat revascularization and myocardial infarction. It is also plausible that reductions in mortality would have been seen with the newer-generation DES.…”
Section: Syntax In the Contemporary Eramentioning
confidence: 99%